Alkylperoxyl spin adducts of pyrroline‐N‐oxide spin traps: Experimental and theoretical CASSCF study of the unimolecular decomposition in organic solvent, potential applications in water. (12th January 2017) - Lescic, Sergiu; Karoui, Hakim; Hardy, Micaël; Charles, Laurence; Tordo, Paul; Ouari, Olivier; Gaudel‐Siri, Anouk; Siri, Didier
Abstract: Spin trapping coupled with electron paramagnetic resonance spectroscopy is the most direct method for detection of very low concentrations of free radicals, and it has been intensively used to detect superoxide or alkylperoxyl radicals in biological systems, using cyclic nitrones as spin traps. The half‐life time of the ensuing spin adducts depends dramatically on the spin trap structure; however, their mechanism of decay has never been definitely established. We investigated at the MRMP2/CASSCF (MultiReference second‐order Møller‐Plesset perturbation theory/Complete Active Set Self Consistent Field) level of theory the mechanism of decay of methylperoxyl and tert‐butylperoxyl spin adducts formed with various cyclic nitrones. We showed that no transition state can be located for the O─O homolytic cleavage, which yields an intermediate biradical with the following sequence O─N─C─O . Then, homolytic cleavage of the N─C bond yields a nitrosoaldehyde, through an early transition state with a very low activation energy. For each nitrone used as spin trap, electrospray ionization mass spectrometry analysis of the spin trapping mixture allowed to detect the presence of the expected nitrosoaldehyde. We generated tert‐butylperoxyl spin adducts in toluene, and we found a good correlation between their half‐life time and the bond dissociation energy of their peroxidic O─O bond. The theoretical method was then extended to hydroperoxyl spin adducts in water and provided promising results. Abstract : We investigated at the MRMP2//CASSCF level of theory the mechanism of decay of methylperoxyl and tert ‐butylperoxyl spin adducts formed with various cyclic nitrones. We showed that no transition state can be located for the O─O homolytic cleavage that yields an intermediate biradical with the following sequence O─N─C─O . Then, homolytic cleavage of the N─C bond yields a nitrosoaldehyde, through an early transition state with a very low activation energy.